Mechanical Force Induced Self‐Assembly of Chinese Herbal Hydrogel with Synergistic Effects of Antibacterial Activity and Immune Regulation for Wound Healing. Issue 21 (1st May 2022) - Chen, Baohui; Zhang, Haifeng; Qiu, Jiajun; Wang, Shaoyun; Ouyang, Liping; Qiao, Yuqin; Liu, Xuanyong
Abstract: Skin wounds, especially infected chronic wounds, have attracted worldwide attention due to the high prevalence and poor treatment outcomes. Hydrogel dressings with antibacterial ability and immune regulation property are urgently required. Herein, inspired by the grinding treatment of traditional Chinese medicine, mechanical force is introduced to promote the effective molecular collision and accelerate the self‐assembly of chitosan (CS) and puerarin (PUE) for fabricating Chinese‐herb‐based hydrogels. The antibacterial rate of CS@PUE (C@P) hydrogel is more than 95%, and the wound closed rate is twice that of the control group. Interestingly, the rational design of C@P hydrogels with different PUE ratios enables a refined control over hydrogel formation, nanofiber appearance, viscoelastic, physicochemical, and biological properties. The extraordinary antibacterial ability of C@P hydrogels may originate from the nanofiber structure and the improved zeta potential on account of the orientation of amino groups in CS . Thus, the synergistically antibacterial and immune regulation properties of C@P hydrogels kill bacteria and relieve inflammation in the wound bed, ensuring the anti‐infection effect, and boosting wound healing. In addition to providing a universal mechanosynthesis of PUE‐based hydrogel for wound healing, this finding is expected to increase the attention paid to Chinese herbal medicines in the construction of biomaterials. Abstract : Inspired by grinding treatment of traditional Chinese medicine, a mechanical force is introduced to promote the effective molecular collision and accelerate the self‐assembly of chitosan (CS) and puerarin (PUE) for fabricating the Chinese‐herb‐based injectable CS@PUE hydrogel. This work provides universal mechanosynthesis of PUE‐based hydrogel with synergistic antibacterial and immune regulation properties for wound healing.